Gene liposome nanocomplex-loaded dermal substitute promotes diabetic chronic wound healing and angiogenesis in rat - Wang, Yong; Ji, Jia-Ying; Guo, Kai; Zhang, Tao; Zhong, Xin-Cao; Zhuang, Ze-Ming; Zhong, Yu-Fan; Lin, Xiao-Ying; Du, Yong-Zhong; Chen, Jian; Tan, Wei-Qiang (Biomedicine & pharmacotherapy, 2023)
The incidence of chronic diabetic wounds is increasing with the growing number of diabetic patients, and conventional wound dressings have proven to be ineffective in treating them. To address this challenge, researchers have developed artificial dermal substitutes using collagen and hyaluronic acid, which are crucial extracellular matrices. However, these subsitiues lack precision and targeted treatment. To overcome this limitation, a gene liposome nanocomplex-loaded dermal substitute (GDS) has been developed as a potential solution. This innovative biomaterial combines the benefits of liposome nanocomplexes with dermal substitutes to offer a more accurate and effective treatment option for chronic diabetic wounds. The GDS has the ability to deliver genes and therapeutic agents specifically to the wound site, promoting angiogenesis and accelerating the wound healing process. Overall, the GDS presents a promising new approach for the clinical treatment of chronic diabetic wounds, offering a targeted and effective solution for this growing problem. [Display omitted] •The scaffold, consisting of collagen and hyaluronic acid, possesses excellent swelling and water absorption properties.•Gene therapy shows promise as a means of overcoming the short-term effects of cytokines.•Versatile SDF-1α expression effectively improves angiogenesis.•The gene-activated wound dressing promotes diabetic wound healing without causing cutaneous contraction.